Maternal Stress, Depression, and Attachment in the Neonatal Intensive Care Unit Before and During the COVID Pandemic: An Exploratory Study - Manuela, Filippa; Barcos-Munoz, Francisca; Monaci, Maria Grazia; Lordier, Lara; Camejo, Maricé Pereira; De Almeida, Joana Sa; Grandjean, Didier; Hüppi, Petra S.; Borradori-Tolsa, Cristina (Frontiers in Psychology, 2021)
The main aim of the present study was to investigate the effects of the COVID-19 pandemic on the mothers’ postnatal depression, stress and attachment during their stay in the Neonatal Intensive Care Unit (NICU). Twenty mothers of very premature infants born before 32 weeks of gestational age were recruited at the Geneva University Hospital between January 2018 and February 2020, before the COVID-19 pandemic started. Mothers were screened for postnatal depression after their preterm infant’s birth (Edinburgh Postnatal Depression Scale, EPDS), then for stress (Parental Stressor Scale: Neonatal Intensive Care Unit, PSS:NICU) and attachment (Maternal Postnatal Attachment Scale, MPAS) at infant’s term-equivalent age. Data were compared with 14 mothers recruited between November 2020 and June 2021, during the COVID-19 pandemic. No significant differences were found in the scores for depression, stress and attachment between the two groups. However, a non-statistically significant trend showed a general increase of depression in mothers during the COVID-19 pandemic, which significantly correlated to the attachment and stress scores. Moreover, the PSS:NICU Sights and Sounds score was significantly positively correlated with EPDS scores and negatively with the MPAS score only in the During-COVID group. To conclude, we discussed a possible dampened effect of the several protective family-based actions that have been adopted in the Geneva University Hospital during the health crisis, and we discussed the most appropriate interventions to support parents in this traumatic period during the COVID-19 pandemic.